External Comparison of Recent Predictive Nomograms for Stone-Free Rate Using Retrograde Flexible Ureteroscopy with Laser Lithotripsy - Erbin, Akif; Tepeler, Abdulkadir; Buldu, Ibrahim; Ozdemir, Harun; Tosun, Muhammet; Binbay, Murat (My University, 2016)
Objective: To assess and compare the applicability of the Resorlu-Unsal Stone Score (RUSS) and the Modified Seoul National University Renal Stone Complexity (S-ReSC) score for flexible ureterorenoscopy (f-URS).